Maximal lactate steady state in running rats - De Manchado, Fúlvia Barros [UNESP]; Gobatto, Claudio Alexandre [UNESP]; Contarteze, Ricardo Vinícius L. [UNESP]; Papoti, Marcelo [UNESP]; Rostom de Mello, Maria Alice [UNESP] (My University, 2005)
The higher concentration during exercise at which lactate entry in blood equals its removal is known as maximal lactate steady state (MLSS) and is considered an important indicator of endurance exercise capacity. The aim of the present study was to determine MLSS in running rats. Adult male Wistar sedentary rats, which were selected and adapted to treadmill running for three weeks, were used. After becoming familiarized with treadmill running, the rats were submitted to five exercise tests at 15, 20, 25, 30 and 35 m/min velocities. The velocity sequence was distributed at random. Each test consisted of continuous running for 25 min at one velocity or until the exhaustion. Blood lactate was determined at rest and each 5 min of exercise to find the MLSS. The running rats presented MLSS at the 20 m/min velocity, with blood lactate of 3.9±1.1 mmol/L. At the 15 m/min velocity, the blood lactate also stabilized, but at a lower concentration (3.2±1.1 mmol/L). There was a progressive increase in blood lactate concentration at higher velocities, and some animals reached exhaustion between the 10 th and 25 th minute of exercise. These results indicate that the protocol of MLSS can be used for determination of the maximal aerobic intensity in running rats.
Keywords: Blood lactate; Maximal aerobic exercise intensity; Running; Wistar rats; lactic acid; animal experiment; controlled study; exercise; exercise test; exhaustion; lactate blood level; male; nonhuman; rat; running; steady state; treadmill